An annotated checklist of the Coccinellidae (Coleoptera) from New Caledonia - Nattier, Romain; Jourdan, Hervé; Mille, Christian; Chazeau, Jean (Zootaxa, 2015)
We present an updated checklist of the ladybird beetle fauna of New Caledonia. Fifty species have been tracked from literature and collections, but six should be removed from the list as they represent false records, invalid or unestablished species: Coccinella boletifera Fauvel, Harmonia conformis (Boisduval), Menochilus duodecimpunctatus (Fauvel), Micraspis lineola (Fabricius), Orcus australasiae Boisduval, and Curinus coeruleus (Mulsant). After our investigations, the current described ladybird beetle fauna totals 44 named species, belonging to 18 valid genera. The endemism rate is 47.7% (21 species), with one endemic subgenus, Scymnus (Caledonus). Based on comparisons of the coccinellid faunas of surrounding regions, the New Caledonian fauna has affinities with Australia and Papua New Guinea more than with the rest of the Pacific area. At least 19 species (43.2%) seem to have been introduced by human activities (either deliberately or accidentally).